Abnormal expression of Tim‐3 antigen on peripheral blood T cells is associated with progressive disease in osteosarcoma patients. Issue 8 (9th July 2016) - Liu, Hongliang; Zhi, Liqiang; Duan, Ning; Su, Pengxiao
Abstract : T‐cell immunoglobulin and mucin‐domain‐3‐containing molecule 3 (TIM‐3) plays a pivotal role in immune regulation and has been found in various tumors. However, the prevalence and distribution of Tim‐3 in osteosarcoma (OS) is still unclear. The aim of this study was to investigate the prevalence and distribution of Tim‐3 in OS. Tim‐3 on peripheral T cells from 82 OS patients and 60 healthy controls were examined by flow cytometry. Plasma levels of IL‐2, IFN‐γ, and TNF‐α were measured by ELSIA. Tim‐3 on both CD4 + T and CD8 + T cells were significantly upregulated in OS patients compared with healthy controls, Tim‐3 + CD4 + T, and Tim‐3 + CD8 + T cells were both negatively associated with serum levels of IL‐2 and IFN‐γ and TNF‐α. In addition, Tim‐3 showed similar levels in patients with different tumor sites. Nevertheless, patients with advanced tumor stage, metastasis, and pathological tumor fracture displayed significantly higher Tim‐3 on both CD4 + T cells and CD8 + T cells than those with early tumor stage, without metastasis and pathological tumor fracture. Moreover, high Tim‐3 on peripheral CD4 + T cells or CD8 + T were significantly related to poor overall survival ( P = 0.014, P = 0.035, respectively). In conclusion, Tim‐3 may be a potential diagnostic and prognostic biomarker for OS progression. Abstract : Tim‐3 is significantly upregulated on CD4 + T and CD8 + T cells from peripheral blood in osteosarcoma patients. Tim‐3 on CD4 + T and CD8 + T cells are negatively correlated with plasma proinflammation cytokines, and positively correlated with tumor stages, metastasis as well as poor overall survival in osteosarcoma patients. Tim‐3 may be a potential diagnostic and prognostic biomarker for osteosarcoma progression.